2017
DOI: 10.3892/mmr.2017.8061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SCN9A gene modification on Na+ channel and the expression of nerve growth factor in a rat model of diarrhea‑predominant irritable bowel syndrome

Abstract: The aim of the present study was to identify whether the sodium voltage-gated channel alpha subunit 9 (SCN9A) gene modification is a potential treatment for diarrhea‑predominant irritable bowel syndrome (D‑IBS), via regulating the Na+ channel and the expression of nerve growth factor (NGF). The recombinant adenovirus vector of the SCN9A gene was established, and rat colon cells were isolated for SCN9A gene modification. All subjects were divided into four groups: i) The SCN9A‑modified (D‑IBS rat model implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis. Accumulating evidence shows that MMP9 [133], S100A12 [148], HP (haptoglobin) [149], OSM (oncostatin M) [150], PRDM5 [151], TSPO (translocator protein) [152], IL18RAP [153], ADAMDEC1 [154], IL1RN [155], SCN9A [156], FADS2 [157], NCF4 [158], SERPINB1 [159], TNFRSF13B [160], IL2RB [161] [133], S100A12 [172], IGF2 [173], GPR84 [174], SOCS3 [175], IGFBP2 [176], HP (haptoglobin) [177], MMP8 [178], OSM (oncostatin M) [179], TLR5 [180], S100A9 [181], PLIN5 [182], NRG1 [183], LCN2 [184], TSPO (translocator protein) [185], PLAU (plasminogen activator, urokinase) [186], PPBP (pro-platelet basic protein) [187], UPP1 [188], ALOX5 [189],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis. Accumulating evidence shows that MMP9 [133], S100A12 [148], HP (haptoglobin) [149], OSM (oncostatin M) [150], PRDM5 [151], TSPO (translocator protein) [152], IL18RAP [153], ADAMDEC1 [154], IL1RN [155], SCN9A [156], FADS2 [157], NCF4 [158], SERPINB1 [159], TNFRSF13B [160], IL2RB [161] [133], S100A12 [172], IGF2 [173], GPR84 [174], SOCS3 [175], IGFBP2 [176], HP (haptoglobin) [177], MMP8 [178], OSM (oncostatin M) [179], TLR5 [180], S100A9 [181], PLIN5 [182], NRG1 [183], LCN2 [184], TSPO (translocator protein) [185], PLAU (plasminogen activator, urokinase) [186], PPBP (pro-platelet basic protein) [187], UPP1 [188], ALOX5 [189],…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 [133], S100A12 [134], SOCS3 [135], MMP8 [136], CRISP3 [137], S100A9 [138], RETN (resistin) [139], IL1RN [140], TLR4 [141], GGT1 [142], CTSD (cathepsin D) [143], FASLG (Fas ligand) [144], CCR4 [145], FCRL3 [146] and ABCF1 [147] were revealed and regarded as diagnostic biomarker in pancreatitis. Accumulating evidence shows that MMP9 [133], S100A12 [148], HP (haptoglobin) [149], OSM (oncostatin M) [150], PRDM5 [151], TSPO (translocator protein) [152], IL18RAP [153], ADAMDEC1 [154], IL1RN [155], SCN9A [156], FADS2 [157], NCF4 [158], SERPINB1 [159], TNFRSF13B [160], IL2RB [161], DLG5 [162], FASLG (Fas ligand) [163], GPR68 [164], IL2RA [161], TCF4 [165], TAGAP (T cell activation RhoGTPase activating protein) [166], ABCB1 [167], FCRL3 [168], ITGB7 [169], PTGER4 [170] and TRAF3IP2 [171] are altered expression in gastrointestinal complications. Recent studies reported that MMP9 [133], S100A12 [172], IGF2 [173], GPR84 [174], SOCS3 [175], IGFBP2 [176], HP (haptoglobin) [177], MMP8 [178], OSM (oncostatin M) [179], TLR5 [180], S100A9 [181], PLIN5 [182], NRG1 [183], LCN2 [184], TSPO (translocator protein) [185], PLAU (plasminogen activator, urokinase) [186], PPBP (pro-platelet basic protein) [187], UPP1 [188], ALOX5 [189], IL1RN [190], CYP1B1 [191], DGAT2 [192], MSRA (methionine sulfoxidereductase A) [193], ADAM9 [194], CPEB4 [195], IRS2 [196], FADS2 [197], SLC22A4 [198], PFKFB3 [199], CTSD (cathepsin D) […”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the other genes involved in the muscle contraction pathway, SCN1A , and SCN9A , can affect sodium channel and expression of nerve growth factor (Cai et al . 2018). In this module GH , GHRHR and SCN4A are downstream of GGaluGA198627 which was found to be associated with the MGR trait.…”
Section: Discussionmentioning
confidence: 99%